Adaptive Governance Based Social Media to Accelerate Stunting Reduction in Medan City - Hajar, Siti (Journal of Political and Governance Studies, 2026)
Background Stunting remains a multidimensional public health problem in Indonesia, including in Medan. It is influenced by factors such as nutrition, sanitation, parenting, food security, and the effectiveness of public policy governance. To date, stunting management has tended to be sectoral, top-down, and has not optimally utilized the potential of digital technology, particularly social media, as a tool for communication, education, and public participation. Methods This research uses a qualitative approach with a case study design in Medan City.   Results Social media functions as an adaptive communication space that accelerates the flow of information, strengthens family nutritional literacy, and opens up two-way feedback between the government and the public. Social media-based adaptive governance practices are characterized by increased policy flexibility, strengthened cross-sector coordination, and growing digital community participation in stunting prevention. Furthermore, this study found that the successful use of social media is largely determined by actor capacity, public trust, and the sustainability of institutional learning. Adaptive Governance based social media is a relevant, innovative, and contextual approach to accelerating stunting reduction in Medan City. Social media has been proven to function not only as a means of disseminating health information but also as an adaptive communication space that enables two- way interaction, continuous policy learning, and strengthened community participation in stunting prevention programs. Conclusions Stunting management in the digital era can no longer be understood solely as a technical health issue, but rather as an adaptive governance process based on learning, collaboration, and two-way communication. In this context, social media serves as a strategic medium that strengthens policy sensitivity to social realities while shortening the gap between policy formulation and implementation.